VectorDistributionStatus_2026 - VectorNet (GBIF Sweden, 2026)
These data represent the current knowledge on the distribution (establishment) status of arthropod vectors at ‘regional’ administrative unit level NUTS3 or equivalent and NUTS2 in Austria, Belgium, Denmark, Germany, The Netherlands, England (UK), Scotland (UK) and Wales (UK), and GAUL outside EU/EEA and Western Balkans and Türkiye, as established by experts based on reports. The eventDate indicates when this status was attributed, and is valid on the date of publishing (May 2026). The NUTS system used is that of 2024 version.
Keywords: Mapping; Occurrence; OCCURRENCE; Biological Sciences; Biologi